A matter of metrics? How analysing per capita energy use changes the face of energy efficient housing in Sweden and reveals injustices in the energy transition. (December 2020) - von Platten, Jenny; Mangold, Mikael; Mjörnell, Kristina
Highlights: The past decade's energy transition is evaluated using two different energy metrics. Low-income households have faced the highest amount of energy savings 2008–2018. kWh/m 2 is the highest in buildings occupied by low-income households. kWh/capita is however the lowest in buildings occupied by low-income households. A change of energy metrics reveals an unjust distribution of the energy transition. Abstract: Improving energy performance of the housing stock continues to be an important undertaking in the energy transition of many EU member states. However, tendencies of low-income households generally living in buildings with low energy performance pose a challenge for this transition, and cases of 'renoviction' and 'green gentrification' are becoming more and more noticed in the scientific community. More so, questions regarding the distributive justice of costs and burdens in the energy transition of the housing stock have been raised. In this paper, we approach this problem from a perspective of energy performance metrics. Although energy performance (kWh/m 2, year) is generally lower in buildings inhabited by low-income households, residential density—and thus building utilisation—tends to be higher. By measuring per capita energy use instead of area-normalised energy use, we investigate if a high residential density can offset a low energy performance and change the perception of which buildings are considered energy inefficient and which are not. Results showed that by measuring per capita energy use instead of area-normalised energy use, energy inefficient buildings were found in high-income city centres instead of in low-income suburbs of Swedish cities. Moreover, there has been an unjust distribution of the imposition of the energy transition over the past decade where the residents with the initially lowest per capita energy use have carried a disproportionately high share of the energy savings. This suggests that a change of energy performance metrics could offer an approach for a more socially just and sustainable energy transition of the housing stock.